2022
DOI: 10.1111/jcmm.17540
|View full text |Cite
|
Sign up to set email alerts
|

SNORA70E promotes the occurrence and development of ovarian cancer through pseudouridylation modification of RAP1B and alternative splicing of PARPBP

Abstract: The present study demonstrated for the first time that SNORA70E, which belongs to box H/ACA small nucleolar noncoding RNAs (snoRNAs) who could bind and induce pseudouridylation of RNAs, was significantly elevated in ovarian cancer tissues and was an unfavourable prognostic factor of ovarian cancer. The over‐expression of SNORA70E showed increased cell proliferation, invasion and migration in vitro and induced tumour growth in vivo. Further research found that SNORA70E regulates RAS‐Related Protein 1B ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It was also shown that DKC1 was able to further promote NB cell survival by increasing SNORA50C expression 100 . In addition, SNORA70E binds DKC1 to regulate Ras‐associated protein 1B (RAP1B) mRNA and increase RAP1B protein level through pseudouridine modification, thereby promoting cancer cell progression in ovarian cancer 101 …”
Section: The Emerging Roles Of Rna Methylation As Critical Regulators...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that DKC1 was able to further promote NB cell survival by increasing SNORA50C expression 100 . In addition, SNORA70E binds DKC1 to regulate Ras‐associated protein 1B (RAP1B) mRNA and increase RAP1B protein level through pseudouridine modification, thereby promoting cancer cell progression in ovarian cancer 101 …”
Section: The Emerging Roles Of Rna Methylation As Critical Regulators...mentioning
confidence: 99%
“… 100 In addition, SNORA70E binds DKC1 to regulate Ras‐associated protein 1B (RAP1B) mRNA and increase RAP1B protein level through pseudouridine modification, thereby promoting cancer cell progression in ovarian cancer. 101 …”
Section: The Emerging Roles Of Rna Methylation As Critical Regulators...mentioning
confidence: 99%
“…However, most of the in vitro studies were performed using primary tumours with a bone tropism, suggesting a role of snoRNAs in metastatic progression in bone. Indeed, experimental modulation of snoRNAs has been shown to regulate migration/invasion in different cancer cell lines derived from prostate (SNORA42, SNORA55) [88,89], breast (SNORA7B, SNORA71A, SNORD50A/B) [90][91][92], lung (SNORA42, SNORA47, SNORA71A, SNORD38, SNORD78) [86,[93][94][95][96], and ovarian cancer (SNORA70E, SNORA72, SNORD89) [97][98][99]. In addition, some of these snoRNAs have also been shown to modulate stemness capabilities in these different cancer types having a bone metastatic tropism (SNORD78, SNORA42, SNORD89, SNORA72, SNORA71A).…”
Section: Mirna and Snorna Expression In Cancer Cells And Their Roles ...mentioning
confidence: 99%
“…Although these signalling pathways are regulated in response to snoRNA modulation, molecular mechanisms behind them remain poorly described and mostly rely on non-canonical activities of snoR-NAs. Another study reported SNORA70E as a promoter of cell migration/invasion by modulating the alternative splicing of PARPBP [97]. As stemness is a key feature in the metastatic progression, it is particularly interesting that a study identified a signature of 22 snoRNAs associated with an elevated activity of the aldehyde dehydrogenase (ALDH) enzyme, a marker of stemness, in tumour-initiating cells from non-small cell lung carcinomas [44,93], suggesting that these snoRNAs are good candidates to be investigated at a functional level.…”
Section: Mirna and Snorna Expression In Cancer Cells And Their Roles ...mentioning
confidence: 99%
“…After growth factor stimulation, c-Fos transcriptional activity occurs within minutes and precedes that of other IEGs [ 19 ]. Additionally, Cav1.2 is associated with the proliferation of bladder SMCs, osteoblasts, and glial cells [ 18 , 20 , 21 ]. The proliferation of HASMCs is beneficial to the stability of vascular function.…”
Section: Introductionmentioning
confidence: 99%